Development and Implementation of an Integrated Model of Perinatal Diabetes Education and Management to Improve Maternity Outcomes and Health Equity - Melanie Browning; Shahrin Sharikha; Kristopher Wu; Stacee Silagi; Victoria Greenberg; Loral Patchen (Health Equity)
Diabetes mellitus (DM) confers unique risks during the perinatal period, contributing to maternal, fetal, and neonatal morbidity and mortality. Integrating DM education and management services with obstetrical care offers key advantages for birthing individuals. The purpose of this study is to describe the development and implementation of a perinatal DM program at a large ambulatory practice serving a diverse population. Understanding this approach and program workflow may facilitate adoption of similar services in other care settings.